Effects of 15-Days −6° Head-Down Bed Rest on the Attention Bias of Threatening Stimulus - Jiang, Shan; Qian, YI-Ming; Jiang, Yuan; Cao, Zi-Qin; Xin, Bing-Mu; Wang, Ying-Chun; Wu, Bin (Frontiers in Psychology, 2022)
Previous researchers have found that head-down bed rest (HDBR) will affect the emotional state of individuals, and negative emotions such as anxiety are closely related to attention bias. The present study adopted the dot-probe task to evaluate the effects of 15-days of -6° head-down bed rest on the attention bias of threatening stimulus in 17 young men, which was completed before (Pre-HDBR), during (HDBR-1, HDBR-8, HDBR-15), after (Post-HDBR) the bed rest. The results showed that the participants’ reaction time of threatening stimulus is significantly longer than neutral stimulus in the HDBR-8, indicating that head-down bed rest may have an effect on the participants’ attention bias, and this effect is manifested as attention avoidance.